TINJAUAN YURIDIS PENOLAKAN PERMOHONAN KASASI DALAM PERKARA KEPAILITAN - Muhammad Kurniawan (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2019)
This study aims to determine the Application of Cassation Appeals in Bankruptcy cases and To determine the Legal Effects of Cassation which were rejected in Bankruptcy cases. This research is a normative legal research that is descriptive and technical or applied. The research approach uses the law approach and case approach. The type of research data is secondary data with primary and secondary legal materials. Data collection techniques such as literature study and data analysis techniques used are deductive. The results of this study explain that the application of the law of the Supreme Court Judge in rejecting the Petition for Cassation in a special civil case Bankruptcy is not appropriate because the Debtor fails to fulfill the contents of the agreement as stipulated in Article 170 paragraph (1) of Law Number 37 of 2004, and the legal consequences of rejection petition for cassation in the case of special bankruptcy civil case, then the petition for cassation submitted by the Cassation Appellant is submitted to the curator as stipulated in Article 69 paragraph (1) of Law Number 37 of 2004 under the supervision of a supervising judge.